Using sentinel cages to estimate infestation pressure on salmonids from sea lice in Loch Shieldaig, Scotland - CC Pert (Inter-Research, 2014)
Sentinel Atlantic salmon, held in cages, were used to estimate the monthly infestation pressure of sea lice at 3 locations along a salmonid migration route in Loch Shieldaig, a Scottish west coast sea loch. The study lasted 30 mo, covering an entire production cycle and fallow period at nearby fish farms. A total of 5007 sea lice were sampled from 3097 sentinel fish, with over 99% of these being Lepeophtheirus salmonis. Infestation pressure was higher in cages nearer the head of the loch and the River Shieldaig estuary. Copepodids were the main infective life cycle stage, but a few (0.5% of total lice sampled) mobile pre-adult and adult stages were also found on the sentinel fish. Infestation pressure on the sentinel fish was correlated with gravid L. salmonis counts from nearby farms. However, there was no evidence that particular events, such as treatments, at the farms led directly to changes in infestation pressure. These findings suggest that, although aquaculture is a contributor of sea lice larvae into the Torridon system, further work is required to determine factors influencing the relationship between farm sea lice levels and infestation pressure in the wider environment.